Mobile at the Base of the Pyramid : Ghana, Mozambique, Nigeria, Zambia Summary Report - World Bank (Washington, DC, 2015)
This report assesses existing mobile application (app) business models targeted at, or suitable for, people living at the base of the pyramid (BoP). The report addresses specific pain points for app developers and provides practical, actionable advice. Its recommendations are specific to each of the four countries: Ghana, Mozambique, Nigeria, and Zambia. While assessing the app markets in the four countries, it became clear that there is a wide range of business models. Each business model is unique to the sector and to the business problem the app is attempting to address. This report focuses on three areas common to all business models to provide maximum value for app developers. This report also presents a brief assessment of app incubators or hubs. These incubators play a significant role in supporting and advocating apps. However, this role is often only partially realized and this report makes recommendations to address this.